The Effect of Rice Straw Extract and drought Levels on Some Vegetative and Flowering Growth Traits and Some Physiological and Biochemical Indicators of Tomato (Solanum esculentum Mill) - Mankhi Jaber, Rasha Najeeb; Fayadh, Murtadha Hussein (American Journal of Biodiversity, 2025)
This study was conducted during the 2024-2025 agricultural season in the Plant Physiology Laboratory in the Department of Life Sciences, College of Education for Pure Sciences, University of Basra. The purpose of this study was to evaluate the effectiveness of three concentrations of rice straw extract (control 0, 5 and 10 g L-1) in reducing the effect of four levels of field capacity (water stress or drought stress, control 100, 75, 50 and 25%). This study aimed to investigate the effect of these two factors and their interactions on vegetative, physiological, and floral growth traits, as well as biochemical indicators of the tomato plant (Salima cultivar). The results were an increase in plant height, number of leaves, and their total area, as well as an increase in water content, leaf content of chlorophyll, carbohydrates, and protein, leaf NPK content, and total number of flowers. Conversely, proline and ABA content and the number of days required for the appearance of the first flower decreased under a concentration of 10 g L-1, especially of the extract. The number of aborted flowers was not significantly affected. The exact opposite occurred under drought levels. The effect worsened with Increased drought, especially below 25%. In addition to the above, the number of aborted flowers increases with increasing drought. As for the interaction between the two activities, concentrations and levels, I tried to extract concentrations, especially 10 g/L-1, and succeeded, albeit slightly, in improving or reducing the negative effects of drought, especially at the 25% level.